Effect of UV radiation on dielectric properties of PU/nano-TiO2 composites - Abdullah, Ahmed Q. (Iraqi Journal of Physics, 2019)
The dielectric constant of most polymers is very low; the addition of TiO2 particles into the polymers provides an attractive and promising way to reach a high dielectric constant. Polymer-based materials with a high dielectric constant show great potential for energy storage applications. Four samples were prepared, one of them was polyurethane (PU) and the other were PU with different weight percent (wt %) of TiO2 (0.1, 0.2, 0.3) powder AFM test was used to distinguish the nanoparticles. The result shows that the most shape of these nanoparticles are spherical and the roughness average is 0.798 nm. The dielectric properties were measured for all samples before and after the exposure to the UV radiation. The result illustrates that the dielectric constant decreased and the dielectric loss increased, the amount of decrease in the dielectric constant decreases with the increasing of the TiO2 concentration that added to the PU and decreasing in the amount of dielectric loss.